Tanggung Jawab Pelaku Usaha kepada Konsumen tentang Keamanan Pangan dalam Perspektif Hukum Perlindungan Konsumen - Aulia Muthiah (Faculty of Law, Maranatha Christian University, 2016)
Food security is very crucial in every aspect of human lives that all humans will fulfill their food needs by producing the food on their own or buy readily consumed food. When consumers consume food, they badly expect foods that are safe for their bodies. We might often encounter consumers who have problems with their health, which sometimes leads them to death due to consuming dangerous foods. A food entrepreneur should be responsible of the mistakes they have made on producing dangerous foods which harm and endanger the health of their consumers, and cause their death at some cases, either the mistakes are on purpose or unintended. The responsibility of entrepreneurs is the responsibility that is based on the harm caused on the consumers and the consumers in this case have to prove the mistake of the entrepreneur. However, there is another alternative of responsibility that ease the consumers, which is called strict liability. This kind of responsibility is a form of risk from the entrepreneur and proving the mistakes should use reverse proof system, in which the entrepreneur is responsible to prove their own mistakes in the food production.